MEDICAL EMERGENCIES IN SUNNAH CUPPING THERAPY: A CLINICAL REVIEW AND ISLAMIC ETHICAL PERSPECTIVE - Andik Isdianto; Novariza Fitrianti (PT. Jurnal Center Indonesia Publisher, 2025)
Sunnah cupping therapy is widely recognized as part of prophetic medicine with spiritual and therapeutic benefits. However, its implementation often overlooks potential medical emergencies, especially when conducted without proper safety protocols. This study aims to identify types of medical emergencies associated with sunnah cupping therapy through a critical literature review. A descriptive-qualitative approach was used, based on a systematic review of scientific publications from 2010 to 2024 obtained from databases such as PubMed, ScienceDirect, and Google Scholar. The results revealed seven major types of complications in cupping practice: infections (local to systemic), severe bleeding and hematoma, vasovagal and hypovolemic shock, allergic reactions, burns (in fire cupping), neurological responses (epilepsy), and dissociative psychological responses (possession). These complications are primarily caused by the lack of medical screening, limited practitioner training, and absence of emergency handling protocols. The study emphasizes the urgency of integrating Islamic ethical values with emergency medical standards in cupping practice. It recommends enhancing public education, practitioner certification, and clinical regulations to ensure patient safety.